A systematic review and meta-analysis comparing the impact of tenofovir and entecavir on the prognosis of hepatitis B virus-related hepatocellular carcinoma patients undergoing liver resection - Hu, Lingbo; Yang, Chao; Qiao, Yingli; Wang, Aidong (Frontiers in Pharmacology, 2024)
Background: Tenofovir (TDF) and entecavir (ETV) are highly effective and welltolerated nucleos(t)ide analogs commonly prescribed for hepatitis virus B (HBV)treatment. Yet, it's unclear if survival outcomes differ for HBV-related hepatocellular carcinoma (HCC) patients treated with ETV or TDF. Thus, this meta-analysis aimed to compare the prognostic effectiveness of ETV and TDF in HBV-related HCC patients.Methods: We comprehensively searched four databases -PubMed, Web of Science, Embase, and the Cochrane Library -to identify pertinent studies utilizing keywords "entecavir," "tenoforvir," "hepatocellular carcinoma," and "liver resection." Our primary outcomes of interest encompassed overall survival (OS), recurrence-free survival (RFS), early recurrence, and late recurrence. The statistical effect size for these measures was expressed in terms of hazard ratios (HR).Results: Our search resulted in 10 studies encompassing 11 datasets involving 7400 patients. Our meta-analysis revealed that patients treated with TDF achieved better OS (HR=0.53; 95% confidence interval (CI) =0.40-0.70, p < 0.0001), RFS (HR=0.68; 95% CI= 0.57-0.80; p < 0.0001), early recurrence (HR=0.80; 95% CI= 0.67-0.94; p < 0.0077), and late recurrence (HR=0.64; 95% CI=0.43-0.97; p = 0.0368). We detected publication bias, potentially affecting OS but not RFS. Conclusion: Our findings demonstrated that TDF outperformed ETV regarding RFS for HBV-related HCC patients. However, to bolster the evidence and establish more conclusive conclusions, further validation via extensive and high-quality randomized controlled trials is essential.